2016
DOI: 10.1097/bot.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Doses Detected at the Eye Level of the Primary Surgeon During Orthopaedic Procedures

Abstract: The risk of harmful levels of radiation exposure at eye level to orthopaedic surgeons is low. This risk is greatest during insertion of femoral intramedullary nails and pelvic fixation, and it is recommended that in these situations, surgeons take all reasonable precautions to minimize radiation dose. The orthopaedic trainees in this study were not subjected to higher doses of radiation than their consultant trainers. On the basis of these results, most of the orthopaedic surgeons remain well below the yearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…Increased operative duration results in increased surgical site infection, as well as more chance in radiation exposure, leading to an increased risk of solid tumors and cataracts. [33][34][35][36] Schilcher et al [37] demonstrated that following AFF, discontinuing BP therapy achieved a 70% per-year reduction in the relative risk of developing contralateral atypical fracture. Dell et al [38] showed the incidence of bilateral AFFs to be 41% in patients who continued BPs for 3 or more years after the index AFF, compared with 19% in patients who discontinued the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Increased operative duration results in increased surgical site infection, as well as more chance in radiation exposure, leading to an increased risk of solid tumors and cataracts. [33][34][35][36] Schilcher et al [37] demonstrated that following AFF, discontinuing BP therapy achieved a 70% per-year reduction in the relative risk of developing contralateral atypical fracture. Dell et al [38] showed the incidence of bilateral AFFs to be 41% in patients who continued BPs for 3 or more years after the index AFF, compared with 19% in patients who discontinued the drug.…”
Section: Discussionmentioning
confidence: 99%
“…In a small operation field like the wrist or the ankle, in which the C‐arm screen represents the osseous structure in total and the extremities position can be changed much more easily to achieve the antero‐posterior and lateral planes than moving the large C‐arm, CGs advantage is lacking. According to the literature, spine surgery and intramedullary nailing of femoral shaft fractures achieved the highest radiation dose and the longest fluoroscopic time . This is due to the fact that in spine surgery, determination of the correct vertebra and pedicle screw placement require numerous fluoroscopic examinations, especially if performed minimally invasively .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, personal safety precautions like keeping a distance from the X‐ray tube to reduce scatter irradiation or wearing lead aprons (ideally torso surrounding, thyroid protecting, lead glasses and leaded gloves for operations, the finger tips might be compromised by direct radiation) still should be considered …”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, lead screens offer the additional benefit of eye protection, which is particularly important for trainee surgeons who have higher eye exposure to radiation than their mentors. 13,14 Lead screens may help to reduce occupational musculoskeletal strain and fatigue. Musculoskeletal injuries among orthopaedic surgeons and residents have been reported mainly in the neck, shoulders, and lower back, [15][16][17] with up to 44% of orthopaedic surgeons reporting musculoskeletal injuries directly attributable to their work.…”
Section: Clinical Relevancementioning
confidence: 99%